The effect of insecticide on adipokinetic hormone titre in the insect body - Kodrík, Dalibor; Socha, Radomír (Pest management science, 2005)
The effect of an insecticide, permethrin (Ambush 25 EC), on the titre of two adipokinetic hormones in the central nervous system (CNS) and haemolymph of the firebug Pyrrhocoris apterus (L) was tested. Doses of 2.5, 12.5 and 25 ng of the insecticide elicited no significant effect on the titre of the adipokinetic peptides in CNS, but caused their dramatic elevation in the haemolymph of both macropterous and reproductive brachypterous bugs. Changes in diapausing brachypterous bugs were minimal and not significant. Using high-performance liquid chromatography (HPLC) and competitive ELISA, both adipokinetic peptides of P apterus (Pyrap-AKH and Peram-CAH-II) were identified and quantified in the CNS of all experimental groups. The ratios of the two peptides in the CNS of the bugs used were affected by insecticide treatment, but in all three groups of bugs the Pyrap-AKH level remained dominant. The insecticide-treated bugs were compared with those exposed to forced running (shaking) and dark shock. Both factors also acted as stressors and enhanced the titre of adipokinetic peptides in the haemolymph but had no effect on hormone titre in CNS. The results indicate an involvement of adipokinetic peptides in the response of insect to various stressors including insecticides.
Keywords: Insecta; Male; Permethrin; vysokoúčinná kapalinová chromatografie; hemolymfa; hmyzí hormony; insekticidy; tma; mužské pohlaví; ELISA; Oligopeptides; Chromatography, High Pressure Liquid; kyselina pyrrolidonkarboxylová; Pyrrolidonecarboxylic Acid; Enzyme-Linked Immunosorbent Assay; Animals; ženské pohlaví; permethrin; hmyz; zvířata; pohybová aktivita; Insect Hormones; Darkness; Motor Activity; centrální nervový systém; Insecticides; Central Nervous System; Hemolymph; Female; oligopeptidy